The Effect of Compensation Training Andjob Satisfaction Towards Employee Retention at Cv. Smile Auto Service Makassar - Ilham Hidayat; Samsul Rizal; Andi Jam'an (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study uses a quantitative method with 61 respondents. The results show that the Training variable (X₁) has a positive and significant effect on Employee Retention (Y), with a regression coefficient value of 0.246 and a significance value of 0.000 <0.050, so that H₀is rejected and H₁is accepted, the Compensation variable (X₂) has a positive and significant effect on Employee Retention, with a regression coefficient value of 0.101 and a significance value of 0.030 <0.050, so that H₀is rejected and H₁is accepted, the Job Satisfaction variable (X₃) has a positive but insignificant effect on Employee Retention, with a regression coefficient value of 0.036 and a significance value of >0.050, so that H₀is accepted and H₁is rejected. Simultaneously, training, compensation, and job satisfaction have a significant effect on employee retention, with a calculated F value > from the F table and a significant value of 0.000 <0.050. These findings indicate that increased training and effective compensation can improve employee retention, while job satisfaction requires strengthening other supporting factors.